2015
DOI: 10.1111/are.12717
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial effects of Oral Allspice,Pimenta dioicapowder supplementation on the hemato-immunological and serum biochemical responses ofOreochromis mossambicus

Abstract: The present study investigated the effects of dietary allspice powder supplementation on welfare status of Tilapia, Oreochromis mossambicus assessed by hemato-immunological and serum biochemical parameters. Five diets were formulated to contain 0 (control), 5, 10, 15 or 20 g of allspice kg À1 of fish feed. Fish were fed experimental diets for 60 days. Supplementation of allspice powder at 10 g kg À1 positively influenced the serum glucose, plasma lysozyme activity and myeloperoxidase activity. Dietary allspice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 34 publications
1
13
0
Order By: Relevance
“…Blood biochemical values are generally used to notice the physiological responses of fish when the growth-enhancing effects of some dietary supplements are tested (Reda et al, 2013;Hoseini et al, 2018). Increased serum total protein, albumin, and globulin levels are directly associated with the improved immune function of fish (Güllü et al, 2015). The present study observed that the diets containing cardamonin significantly increased serum albumin levels.…”
Section: Discussionsupporting
confidence: 49%
See 2 more Smart Citations
“…Blood biochemical values are generally used to notice the physiological responses of fish when the growth-enhancing effects of some dietary supplements are tested (Reda et al, 2013;Hoseini et al, 2018). Increased serum total protein, albumin, and globulin levels are directly associated with the improved immune function of fish (Güllü et al, 2015). The present study observed that the diets containing cardamonin significantly increased serum albumin levels.…”
Section: Discussionsupporting
confidence: 49%
“…The present study observed that the diets containing cardamonin significantly increased serum albumin levels. These results would indicate the modulation of nonspecific defense mechanisms or protein metabolism by cardamonin in fish (Güllü et al, 2015;Sarvi Moghanloa et al, 2018). Serum cholesterol, HDL, and LDL levels are commonly used as indicators of lipid metabolism and lipid peroxidation in fish (Mutlu et al, 2015;Lim et al, 2019).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Similar impairment of high phytotherapic doses (20 g/kg, allspice powder) on respiratory burst was observed for O . mossambicus (Güllü et al, 2016). Although not significant, a similar trend can be observed for lysozyme.…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, many recent aquaculture studies have focused on the search for organic‐based antimicrobial, antifungus, immunostimulant, anti‐inflammatory and stress‐relieving products that will provide maximum benefits (Asadi, Mirvaghefei, Nematollahi, Banaee & Ahmadi, ; Balamurugan et al., ; Hernández, Romero, Gonzalez‐Stegmaier & Dantagnan, ; Kirubakaran, Subramani & Michael, ). Generally, in these studies, microorganisms, plants and plant extracts, volatile oils, active substances or polysaccharides were investigated (Acar, Kesbiç, Yılmaz, Gültepe & Türker, ; Bilen, Ünal & Güvensoy, ; Güllü et al., ; Gültepe et al., ; Sönmez, Bilen, Alak et al., ). These products contain polypeptide, phenolic, polyphenolic, terponoid, quinone, lectin and alkaloid derivatives and have potential as an alternative to synthetic drugs for use in aquaculture (Citarasu, ).…”
Section: Introductionmentioning
confidence: 99%